Back Cover: Metal‐free and Scalable Synthesis of Porous Hyper‐cross‐linked Polymers: Towards Applications in Liquid‐Phase Adsorption (ChemSusChem 20/2015). Issue 20 (12th October 2015) - Schute, Kai; Rose, Marcus
<x xml:space="preserve">Abstract</x> The Back Cover picture shows how highly hydrophobic porous polymers can selectively adsorb specific molecules from aqueous solutions. The hydrophobic effect of the polymer is also indicated and visualized by the non‐wettable coating of the fingers with the original hydrophobic polymer. In this work a metal‐free route for the synthesis of porous hyper‐cross‐linked polymers (HCP) with specific surface areas of up to 1842 m2 g−1 was developed. The reduced surface polarity enhances the selectivity in the liquid‐phase adsorption of the biogenic platform chemical 5‐hydroxymethylfurfural and, thus, rendering this separation technology suitable for future biorefineries.